Aspectos da fresagem em pavimentos reforçados com geossintéticos e impacto do fresado (RAP) nas propriedades de misturas asfálticas recicladas - Souza, Tiago Rodrigues (2024)
With the growing use of geosynthetic interlayers, such as geogrids, geotextiles and paving geocomposites in asphalt rehabilitation projects, there is an anticipated increase in cases where asphalt layers containing these interlayers need to be milled. While there is substantial experience in milling traditional asphalt layers, the presence of polymeric or fiberglass interlayers introduces new challenges to pavement engineering. As a result, understanding how the milling process for asphalt layers with geosynthetic interlayers differs from conventional asphalt milling has become increasingly important. The milled material, referred to as Reclaimed Asphalt Pavement (RAP) when containing geosynthetics, here nominated G-RAP, exhibits unique characteristics that differentiate it from conventional RAP. Due to the limited information on the milling processes and characteristics of RAP produced from geosynthetic-reinforced pavements, it is essential to explore the millability of these reinforced pavements and the challenges associated with milling them. Furthermore, research should be conducted to assess the feasibility of reusing G-RAP in the production of new recycled asphalt mix. This study involved constructing an experimental test track with five different geosynthetic-reinforced asphalt sections at Salvador International Airport in Brazil. The findings indicated that all geosynthetic interlayers were capable of being milled without causing inefficiencies in the milling operations. Successful milling was achieved by operating at the maximum milling speed of 320 rpm, with the use of water. Fiberglass products were observed to mill effectively, while polymeric products showed minor entanglements. It is recommended that the milling depth be at least 25 mm below the geosynthetic position within the asphalt layers. G-RAPs were collected and characterized, showing physical differences and positive mechanical influences in new HMA mixtures recycled with 20% G-RAP, particularly in Marshall stability, Indirect Tensile Strength, and Resilient Modulus Marshall stability. The results of the present study confirm that geosynthetic-reinforced asphalt layers are millable, with potential for the reuse of the generated G-RAP in new asphalt mixtures.